Prognostic implication of p27(Kip1), Skp2 and Cks1 expression in renal cell carcinoma: a tissue microarray study - Liu, Zheng (BioMed Central, 2008)
BACKGROUND: p27(Kip1 )plays a major role as a negative regulator of the cell cycle. The regulation of p27(Kip1 )degradation is mediated by its specific ubiquitin ligase subunits S-phase kinase protein (Skp) 2 and cyclin-dependent kinase subunit (Cks) 1. However, little is known regarding the prognostic utility of p27(Kip1), Skp2 and Cks1 expression in renal cell carcinoma. METHODS: Immunohistochemistry was performed for p27(Kip1), Skp2 and Cks1 in tissue microarrays of 482 renal cell carcinomas with follow-up. The data were correlated with clinicopathological features. The univariate and multivariate survival analyses were also performed to determine their prognostic significance. RESULTS: Immunoreactivity of p27(Kip1), Skp2 and Cks1 was noted in 357, 71 and 82 patients, respectively. Skp2 and Cks1 expression were not noted in chromophobe cancers. A strong correlation was found between Skp2 and Cks1 expression (P < 0.001), both of which were inversely related to p27(Kip1 )levels (P = 0.006 and P < 0.001), especially in primary and clear-cell cancers. Low p27(Kip1 )expression and Skp2 expression were correlated with larger tumor size and higher stage, as well as tumor necrosis. Cks1 expression was only correlated with tumor size. In univariate analysis, low p27(Kip1 )expression, Skp2 and Cks1 expression were all associated with a poor prognosis, while in multivariate analysis, only low p27(Kip1 )expression were independent prognostic factors for both cancer specific survival and recurrence-free survival in patients with RCC. CONCLUSION: Our results suggest that immunohistochemical expression levels of p27(Kip1), Skp2 and Cks1 may serve as markers with prognostic value in renal cell carcinoma.